A Web Browser Fingerprinting Method Based on the Web Audio API. (22nd January 2019) - Queiroz, Jordan S; Feitosa, Eduardo L
Abstract: Web Browser Fingerprinting is a process in which the users are, with high likelihood, uniquely identified by the extracted features from their devices, generating an identifier key (fingerprint). Although it can be used for malicious purposes, especially regarding privacy invasion, Web Browser Fingerprinting can also be used to enhance security (e.g. as a factor in two-factor authentication). This paper investigates the use of Web Audio API as a Web Browser Fingerprinting method capable of identifying the devices. The idea is to prove or not if audio can provide features capable to identify users and devices. Our initial results show that the proposed method is capable of identifying the device's class, based on features like device's type, web browser's version and rendering engine.